Ptf1a Binds to and Activates Area III, a Highly Conserved Region of the Pdx1 Promoter That Mediates Early Pancreas-Wide Pdx1 Expression - Wiebe, Peter O. (American Society for Microbiology, 2007)

(untitled)
The critical pancreatic transcription factor Pdx1 is expressed throughout the pancreas early but enriched in insulin-producing β cells postnatally. Previous studies showed that the 5′ conserved promoter regions areas I and II (Pdx1(PB)) direct endocrine cell expression, while an adjacent region (Pdx1(XB)) containing conserved area III directs transient β-cell expression. In this study, we used Cre-mediated lineage tracing to track cells that activated these regions. Pdx1(PB)Cre mediated only endocrine cell recombination, while Pdx1(XB)Cre directed broad and early recombination in the developing pancreas. Also, a reporter transgene containing areas I, II, and III was expressed throughout the embryonic day 10.5 (E10.5) pancreas and gradually became β cell enriched, similar to endogenous Pdx1. These data suggested that sequences within area III mediate early pancreas-wide Pdx1 expression. Area III contains a binding site for PTF1, a transcription factor complex essential for pancreas development. This site contributed to area III-dependent reporter gene expression in the acinar AR42J cell line, while PTF1 specifically trans-activated area III-containing reporter expression in a nonpancreatic cell line. Importantly, Ptf1a occupied sequences spanning the endogenous PTF1 site in area III of E11.5 pancreatic buds. These data strongly suggest that PTF1 is an important early activator of Pdx1 in acinar and endocrine progenitor cells during pancreas development.